Isolation and characterization of the ribosomal protein gene, RPL37A, from human nasopharyngeal-derived cell lines - Kiung, Siong Siang (Universiti Malaysia Sarawak (UNIMAS), 2012)
Previous studies have shown that expression of RPL37A gene was downregulated in nasopharyngeal carcinoma cell lines and it had been reported that genetic mutation of coding sequences in ribosomal protein gene RPSJ9 is the cause of dysregulation of gene expression in Diamond-Blackfan Anemia. The objective of this study is to determine whether mutation in coding sequences of RPL37A gene is the cause of its differential expression in nasopharyngeal carcinoma by isolating, sequencing and analyzing the coding sequences of the gene from normal nasopharyngeal epithelial cell lines and nasopharyngeal carcinoma cell lines. Results from this study show that there is no difference in the nucleotide sequence in the coding region of RPL37A gene from both types of nasopharyngeal cell lines and therefore indicates that mutation in the coding region of the RPL37A gene is not the cause of its differential expression in nasopharyngeal carcinoma.